The effect of information technology on the quality of financial reports in the regional financial management agency of Takalar Regency - Syamsuddin Syamsuddin (Privietlab, 2022)
This study aims to determine the effect of information technology on the quality of financial reports. The research was conducted at the Regional Financial Management Agency (BPKD) of Takalar Regency. This type of research is quantitative research. The data collected is primary data by distributing questionnaires to respondents. The number of respondents in this study were 45 people. To test the hypothesis using a simple linear regression approach and the data is processed using the SPSS application. The results of the study indicate that information technology has a positive and significant effect on the quality of financial reports.